Analysis of Coffee Consumption Motives on Coffee Drinking Habits among Workers - Ivana Shintya Nathania Hutajulu; Ira Marti Ayu; Decy Situngkir; Erna Veronika (Journal of Public Health for Tropical and Coastal Region, 2026)
Introduction: Coffee is a popular beverage among the public; however, excessive consumption can have negative effects. A preliminary survey showed that six out of ten respondents (60%) had poor coffee consumption. This study aimed to identify the factors associated with coffee consumption at X Company in 2025.Methods: This study was conducted from May to June 2025. A cross-sectional study design was employed with a total sample of 68 participants. The dependent variable was coffee consumption, and the independent variables were habit, mood, alertness, social, symptom management, and taste. The sampling technique used was total sampling method. Data were analyzed using univariate and bivariate analyses with chi-square tests.Results: Data analysis revealed that 79.4% of workers had poor coffee consumption. Further analysis revealed factors that influence it, including habit  (PR=1.47, 95% CI=0.9-2.21), mood (PR=1.38, 95% CI=1.0-1.88), alertness (PR=1.41, 95% CI=0.9-2.00), social (PR=1.38, 95% CI=1.00-1.88), symptom management (PR=1.69, 95% CI= 0.9-3.17), and taste (PR=1.58, 95% CI=1.03-2.42).Conclusion: Habit, mood, alertness, social factors, symptom management, and taste were associated with coffee consumption among workers at Company X. It is recommended that workers reduce their daily coffee consumption and limit sugar use when drinking coffee to minimize the long-term effects of excessive coffee consumption on health of workers.